Performance assessment of glass powder as filler in AC-WC asphalt exposed to Bekasi River Water - Ardhya Alga Lingga; Hadi, Muhamad Abdul (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2025)
Frequent flooding in Indonesia causes significant infrastructure damage, including deterioration of asphalt pavements. Bekasi City was selected as the study area due to its river system characteristics, which make the region highly susceptible to prolonged inundation. This study evaluates glass powder (GP) as an alternative filler in AC-WC mixtures and examines performance under simulated flooding. Five GP substitution levels (0%, 25%, 50%, 75%, and 100%) were tested and immersed in Bekasi River water for 0, 24, and 48 hours. Performance was assessed through Marshall Standard (MS), Indirect Tensile Strength ( ITS), Index of Retained Strength (IRS), Tensile Strength (TSR), and Cantabro Loss (CL) testing. Results show that GP affects all performance parameters, with 75% substitution exhibiting the best behavior among modified mixtures. However, all GP mixtures showed lower stability and ITS compared to the control, and full substitution (100%) resulted in the greatest performance decline. Longer immersion further reduced stability, ITS, TSR, and IRS while increasing flow, indicating higher moisture susceptibility. CL decreased with GP addition except at 100% substitution or extended immersion, where mass loss increased. Overall, while 75% GP substitution showed the best relative performance and remained functional up to 24 hours of immersion, long-term soaking led to significant degradation. GP shows potential as a sustainable filler, but improvements are required for use in flood-prone areas.